Sino-Nasal Squamous Cell Carcinoma (SNSCC): a retrospective review of the treatment outcomes of patients treated at Groote Schuur Hospital, Cape Town, South Africa - Nagar, Bhavesh (Division of Radiology, 2023)
Purpose: Cancers of the sinonasal tract are rare, comprise a diverse group of histologies and are known for their poor prognostic outcomes. The primary aim of this study was to evaluate the 2- and 5-year overall survival (OS) rates in patients treated with radical and palliative intent for sinonasal squamous cell carcinoma (SNSCC). Methods: A retrospective review of medical records of all patients presenting to Cape Town's Groote Schuur Hospital between January 2003 and December 2013 was carried out. All patients with histologically proven squamous cell carcinoma (SCC) of the maxillary sinus and nasoethmoidal complex who underwent treatment at Groote Schuur Hospital and/or iThemba LABS (Laboratory for Accelerator Based Sciences) were included. Fifty-five patients with cancers of the sinonasal tract were identified from the electronic patient system; 23 were excluded either because of different histologies, lack of histology or having initiated treatment outside of Groote Schuur Hospital. The medical records of 32 patients were utilised for final analysis. 2- and 5-year OS was calculated using Kaplan-Meier analysis. Results: The majority (75%) of patients had an ECOG performance status of 1 with facial asymmetry secondary to tumour mass or swelling being the most common presenting symptom (present in 68,75% of cases). 62,50% of cases originated within the maxillary antrum and 56,25% of cases were classified as keratinizing SCC. Twenty-six (81,25%) patients presented with stage IV disease; nodal disease was seen in 13 (40,63%) patients and distant metastasis in 4 (12,50%) patients. Most patients underwent palliative intent treatment with only 11 (34,38%) having radical treatment. The cumulative 2- and 5-year OS from the date of treatment initiation was 26% and 19% respectively. Median OS for the entire cohort was 7,7 months and was statistically significant between intent groups at 5,19 months (95% CI:3.43– 6.95) for palliative compared to 35,45 months (95% CI: 0.00–138.52) for radical patients (c2 = 7.80, p = 0.005). Conclusion: Despite a decline in incidence of disease over the last 30 years and the improved diagnostic and therapeutic modalities available today, the prognosis and survival outcomes for SNSCC remains poor.